Crop diversification affects biological pest control - Marković Dimitrije (Agroznanje, 2013)
Crop monocultures encourage the multiplication and spread of pest insects on massive and uniform crop. Numerous studies have evaluated the impact of plant diversification on pests and beneficial arthropods population dynamics in agricultural ecosystems and provided some evidence that habitat manipulation techniques like intercropping can significantly influence pest control. This paper describes various potential options of habitat management and design that enhance ecological role of biodiversity in agroecosystems. The focus of this review is the application and mechanisms of biodiversity in agricultural systems to enhance pest management.